Role of Old Antibiotics in the Era of Antibiotic Resistance. Highlighted Nitrofurantoin for the Treatment of Lower Urinary Tract Infections - Maria Jose Munoz-Davila (MDPI AG, 2014)
Bacterial infections caused by antibiotic-resistant isolates have become a major health problem in recent years, since they are very difficult to treat, leading to an increase in morbidity and mortality. Nitrofurantoin is a broad-spectrum bactericidal antibiotic that, through a complex mode of action which is not completely understood, affects both Gram-negative and Gram-positive bacteria. Nitrofurantoin has been used successfully for a long time for the prophylaxis and treatment of acute lower urinary tract infections in adults, children and pregnant women, but the increased emergence of antibiotic resistance has made nitrofurantoin a suitable candidate for the treatment of infections caused by multidrug-resistant pathogens. Here, we review the mechanism of action, antimicrobial spectrum, pharmacology and safety profile of nitrofurantoin. We also investigate the therapeutic use of nitrofurantoin, including recent data which highlight its role in the management of community urinary tract infection, especially in cases of multidrug-resistant isolates, in which oral active antimicrobials are limited resources nowadays.